An Analysis of Cooperative Principle in Back to the Outback Movie: Pragmatic Approach - Ervina Safitri; Ambalegin Ambalegin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
In this study, the cooperative principles described by the characters in the Back to the Outback movie are implemented using Grice's theory. The research uses qualitative descriptive to explain the data. Sudaryanto collected data using non-participatory and observational methods. The data was then examined using the Pragmatic Identity Method and the Matching method. The data were examined in context using the pragmatic identity method. There are four types of maxims in the cooperative principle found. the total maxim of data is 32 data. the results found maxim of quantity data as much as 9 data, maxim of quality 6 data, maxim of manner 10 data, maxim of relation 7 data. The most widely used data is the maxim of manner. Lastly, the maxim of quality is the data that is used the least by the characters in the Back to the Outback movie.